Effects of Negotiation for Meaning Towards the Improvement of Classroom Interactional Skills - Tze, Pung Ching Joanna (2003)
Interaction involves not just the expression of ideas but the skills in solving communication problems that occur. There is an opportunity to transfer information efficiently and ensure mutual understanding in communication when students negotiate for meaning. This study examined how students receiving negotiation of meaning training contributed significantly on a test of two-way information task. This study involved 40 students of the English Academic Purpose course from the Universiti Putra Malaysia. The purpose of Chapter 1 is to provide an introductory overview of the study. In particular, the background of this study, statement of the problem, the purpose and the significance of this study are discussed. Chapter 2 covers the related theories and past studies on negotiation of meaning. The discussion of the related theories are well established in the second language learning field which view the vital role of negotiation for meaning in achieving communicative competence. Chapter 3 deals with the research design and the procedures of the methodology in this study. This was a pretest-posttests quasi-experimental design conducted on two intact groups of students. The study was carried out over a period of seven weeks. The instrument used was a set of adapted two way information task. Chapter 4 presents the findings of the data. Percentage, mean, standard deviation, independent sample t-test and repeated measures analysis of variance were employed to analyse the data. The study concluded that negotiation of meaning training contributed significantly to the students' achievement in the two-way information task.